The Endocannabinoid Anandamide Attenuates Acute Respiratory Distress Syndrome by Downregulating miRNA that Target Inflammatory Pathways - Sultan, Muthanna; Alghetaa, Hasan; Mohammed, Amirah; Abdulla, Osama A.; Wisniewski, Paul J.; Singh, Narendra; Nagarkatti, Prakash; Nagarkatti, Mitzi (Frontiers in Pharmacology, 2021)
Acute respiratory distress syndrome (ARDS) is defined as a type of respiratory failure that is caused by a variety of insults such as pneumonia, sepsis, trauma and certain viral infections. In this study, we investigated the effect of an endocannabinoid, anandamide (AEA), on ARDS induced in the mouse by Staphylococcus Enterotoxin B (SEB). Administration of a single intranasal dose of SEB in mice and treated with exogenous AEA at a dose of 40mg/kg body weight led to the amelioration of ARDS in mice. Clinically, plethysmography results indicated that there was an improvement in lung function after AEA treatment accompanied by a decrease of inflammatory cell infiltrate. There was also a significant decrease in pro-inflammatory cytokines IL-2, TNF-α, and IFN- and immune cells including CD4+ T cells, CD8+ T cells, Vβ8+ T cells, and NK+ T cells in the lungs. Concurrently, an increase in anti-inflammatory phenotypes such as CD11b+Gr1+ Myeloid-derived Suppressor Cells (MDSCs), CD4+FOXP3+ Tregs, and CD4+IL10+ cells was observed in the lungs. Microarray data showed that AEA treatment in ARDS mice significantly altered numerous miRNA including downregulation of miRNA-23a-3p, which caused an upregulation of arginase (ARG1), which encodes for arginase, a marker for MDSCs, as well as TGF-β, which induces Tregs. AEA also caused down-regulation of miRNA-34a-5p which led to induction of FoxP3, a master regulator of Tregs. Transfection of T cells using miR 23a-3p or miRNA-34a-5p mimics and inhibitors confirmed that these miRs targeted ARG1, TGFβ2 and FoxP3. In conclusion, the data obtained from this study suggests that endocannabinoids such as AEA can attenuate ARDS induced by SEB by suppressing inflammation through down-regulation of key miRNA that regulate immunosuppressive pathways involving the induction of MDSCs and Tregs.